Composition and abundance of the zooplankton in lagoon El Morro, Margarita Island, Venezuela - Villalba, William (2017)
The composition and abundance of the zooplankton of El Morro lagoon on the island of Margarita, Venezuela, during the upwelling period (March-May 2011) and relaxation (June-August 2011) were analyzed. Samples were collected at 6 stations in different areas of the lagoon. Sampling was performed with a 333 μm plankton net for 10 minutes. Water Temperature, salinity and dissolved oxygen were measured in situ, in addition to nutrients. Average water temperature values of 29.7 °C, a salinity of 36 ups, and dissolved oxygen of 5.9 mg.L-1 were found. The concentration of nutrients was low (averages of 0.12, 0.04, 0.03 mg.L-1 for nitrate, nitrite and phosphate, respectively). Significant seasonal differences were detected with greater records in the relaxation season, whereas spatially did not show differences, although in the internal stations a greater abundance was recorded. Fifteen zooplankton groups were identified, identifying nine species of Copepoda, two of Cladocera, one of Decapoda, Tunicada and Rotifera and different larval forms of different taxa. Crustacean larvae showed the highest average and relative abundance (47738 ind.m-3 y 46.83%, respectively), followed by copepod O. nana (31740 ind.m-3 and 25.94%, respectively) and P. quasimodo (12958 ind.m-3 and 8.47%, respectively). This lagoon involves the emergence-relaxation seasonality as an important effect on the distribution and abundance of zooplankton.